HUBUNGAN PERILAKU IBU BALITA TENTANG PEMANFAATAN POSYANDU DENGAN STATUS GIZI BALITA DI POSYANDU MUTIARA KASIH KELURAHAN KIBING WILAYAH KERJA PUSKESMASBATU AJI KOTA BATAM TAHUN 2017 - Hildayanti, Hildayanti; Aulia, Devy Lestari Nurul (Universitas Batam, 2017)
The compliance of mother to take their under five-year old children to the posyandu is very beneficial for monitoring their children nutritional status. It is as an attempt to improve their nutritional status by routinely giving their compulsory vitamins and vaccinations. Accordingly, this research aims to know the correlation of mothers’ attitude to take the under-five year old children to posyandu and their children nutritional status. This study employed Cross Sectional study approach and was conducted on June 2017 in Mutiara Kasih Integrated Health Post of Batu Aji, Batam. The total population investigated was 244 mothers with under-five year old children attended this post, meanwhile, the sample was 144 toddlers selected through simple random sampling technique. The data was collected by questionnaires and measured with anthropometrical scales. Precisely, this study used univariate and bivariate data analysis of Chi Square test on 95% significance level. The result presents that 82% children have good nutritional status, 14% are lack of nutrition, and 4% experience malnutrition verified by p-value of 0.000. In conclusion, there is a significant correlation between the attitude of mother to take their under-five year old children to integrated health post or posyandu and their children nutritional status. At last, it is recommended that the mothers to be more active in attending and taking their children to the posyandu to ensure the children have their nutrition fulfilled to support their growth.